Paraurethral cysts in women. Etiopathogenesis, diagnosis and treatment - Konecki, Tomasz; Salagierski, Maciej; Sosnowski, Marek (Menopause Review/Przegląd Menopauzalny, 2005)
Urethral cyst-like structures are very common. However, due to their asymptomatic behaviour, they are diagnosed not very frequently. Among the symptoms we can find a palpable or visible mass, pain of women sexual organs, dysuria, dyspareunia and miction disorders. Paraurethral cysts can be either congenital or acquired, although it is difficult to distinct between the two. Acquired cysts of the vagina are the most common paraurethral cystic lesions with a traumatic etiology. Microscopically, these cysts are lined by squamous multi-layer epithelium and they can contain caseous or purulent material. Equally congenital paraurethral cysts are most uncommon. They originate from various embryologic components and vestigial remnants of the vagina and the female urethra. Their backround is mostly from paramesonephric (Mullerian) ducts, sometimes from persistent mesonephric (Gartner’s) ducts or paraurethral (Skene’s) glands. In paraurethral cysts diagnosis, apart from physical examination, transvaginal ultrasound and urethroscopy or urethrocystography are used. Differential diagnosis of paraurethral cysts is relevant and includes: urethral diverticula, urethrocele, prolapsed ectopic ureterocele and paraurethral tumors. Treatment is recomended if the cysts are symptomatic. Endoscopic management, consisting of cyst marsupialization, in order to obstruct its cavity, or surgical excision is performed. Therapeutic results are good and in most cases women are completely asymptomatic after the procedure.